Digital technology to construct 3D hydrodynamic models for monitoring environmental flows - Wade, M.; Kaizer, A.; McNeil, T.; O’Brien, G. (CGIAR Initiative on Digital Innovation, 2022)
To support the implementation of environmental flows (e-flows), we piloted a three-dimensional digital modeling approach to monitor the changes in river ecosystems. A high-resolution 3D model of study sites in the Crocodile River, South Africa, was constructed and used to test its utility and value to monitor changes in river ecosystem structure over time. The initial demonstration of the approach shows highly detailed 3D models of nine tracks across the study sites. The output represents the velocity-depth and bathymetry variability of each site in 3D. The dataset successfully demonstrated the potential value of adopting the approach for e-flow implementation to monitor the habitat dynamism to support the timely management of river health. In the next phase, this assessment will integrate the 3D modeling approach into a hydrodynamic modeling framework to investigate dynamic relationships between flow-ecosystem and ecosystem services.